Energy and time saving processing: A combination of hot isostatic pressing and heat treatment. Issue 5 (September 2017) - Weddeling, Anna; Theisen, Werner
Abstract : The technique of hot isostatic pressing (HIP) is used to simultaneously heat up and apply high isostatic pressure to a metallic or ceramic entity in order to reach compaction. The integration of heat treatment into the compaction process generates much curiosity in the HIP community. This paper resumes the different methods for accelerated cooling and gives an overview of the research done with integrated heat treatment. Results in the field of steels, lightweight alloys and superalloys are resumed.